A produção para autoconsumo na agricultura familiar: uma questão de liberdade alimentar - Fiorese, Josiane Gracieli Preschlak (2017)
The production of self-consumption is a classic practice of social reproduction of family agriculture, and this type of production plays important roles in the contemporary rural environment, despite the profound changes that have occurred over the years. In Brazil the production of self-consumption is present in most agricultural establishments, being more prevalent in family farms. In this sense, the central hypothesis of this study is based on the perception that self-consumption has a "strategic function of developing family unity and expanding the substantive freedoms of family farmers." This hypothesis is associated with a set of objectives, the main one being to analyze the perception of agroecological, organic and integrated farmers in relation to the production of food for self consumption. Hence three specific objectives: to identify the meanings of producing food for self-consumption in family agriculture; To compare food production for self-consumption of agroecological and integrated farmers; To analyze production for self-consumption as a strategy carried out by farmers for the development of the family unit. The target subjects of the present research represent three distinct groups of farmers: agroecological, organic and integrated. As for the integrated, we refer to poultry farmers, since they represent the main segment of the region in this category. Data collection was done through interviews with individuals from municipalities of the Capanema Microregion, representatives of each group mentioned above. The construction of the Collective Subject Discourse (DSC), which is based on the theory of social representations, was used as a methodological strategy in qualitative research. As a result, the Discourse of the Collective Subject is presented, and the discussion about the elements found in each question was emphasized and emphasized the relation of these perceptions with a perspective of development presented by Amartya Sen in his book "Development as Freedom". Regarding the final considerations, we can highlight that the production of food for self consumption is prevalent in family agriculture, and the intensity, form and reasons for which it is practiced is peculiar to each place and group of individuals, however it is possible to identify that both The segments have shared ideas, where we can highlight central ideas related to this theme and produce a discourse of the collective subject. Therefore, it is understood that the production for self-consumption in family farming has several meanings (biological, environmental, political, social, cultural, economic and ethical), that is, it is a matter of food freedom.